2009
DOI: 10.1111/j.1464-410x.2008.08236.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinephric and renal sinus fat infiltration in pT3a renal cell carcinoma: possible prognostic differences

Abstract: effects of PN, RS or RS + PN fat infiltration, univariable and multivariable Cox proportional hazard regression models were applied, including lymph node status, metastases, presence of sarcomatoid features and tumour necrosis, Fuhrman's grade, Karnofsky performance status, and tumour size. RESULTSPN fat invasion alone was present in 58, RS in 21, and PN + RS in 27 patients. The median follow-up was 2.9 years; 49 patients died from RCC. In univariable and multivariable analyses RS fat infiltration was an unfav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 27 publications
2
33
1
4
Order By: Relevance
“…In clinical situations, RCC often metastasizes to bone, which may cause pain, bone fracture, immobility, and decreased quality of life. Our IHC results showed that ON expression led to a significantly higher chance of renal vein sinus invasion, which is known to be related to worse prognosis [28]. Taken together, these results suggest that ON expression in RCC may show higher potential for invasion and future metastasis.…”
Section: Discussionmentioning
confidence: 74%
“…In clinical situations, RCC often metastasizes to bone, which may cause pain, bone fracture, immobility, and decreased quality of life. Our IHC results showed that ON expression led to a significantly higher chance of renal vein sinus invasion, which is known to be related to worse prognosis [28]. Taken together, these results suggest that ON expression in RCC may show higher potential for invasion and future metastasis.…”
Section: Discussionmentioning
confidence: 74%
“…In einer sog. "imperativen Situationen" waren eine schlechte Tumordifferenzierung (Fuhrman Grad 3) sowie das bilaterale Auftreten von Nierentumoren mit einem schlechteren Gesamtüberle-ben vergesellschaftet [16,17,18]. Andere Untersuchungen zeigten z.…”
Section: Bisheriger Nutzen Der Urologischen Tumordatenbankunclassified
“…Im lokalisierten pT2-Stadium erfolgt nun erstmals eine Unterteilung der Tumoren in ein pT2a und pT2b mit einem Cutt-off der Tumorgröße von 10 cm, nachdem eine prognostische Unterscheidung innerhalb der T2-Gruppe anhand des Tumordurchmessers gezeigt wurde [19]. Im pT3a-Stadium wird weiterhin zwischen perirenaler und/oder peripelviner Fettgewebeinfiltration unterschieden [1].…”
Section: Tnmklassifikationaktuelle äNderungenunclassified